Education and social service use patterns of children and youth with neurodevelopmental disorders - Jia, Ruiting; Werk, Christine; O'Brien, Daniel; Jagodzinski, Robert; Piatt, Carley (International Journal of Population Data Science, 2018)
Introduction This study uses linked administrative data to identify Albertan children and youth (aged 0 to 25 years) with Autism Spectrum Disorder (ASD), Cerebral Palsy (CP) or Fetal Alcohol Spectrum Disorder (FASD), and to examine their government service use patterns from 2005/06 to 2010/11. Objectives and Approach The analysis looks at whether children with ASD, CP and FASD have similar government service use patterns and how their service use patterns changed over time. Six Government of Alberta ministries’ data were linked (Health, Justice, Education, Advanced Education, Children’s Services and Community and Social Services). Individuals were defined as having ASD, CP or FASD if, at any point during the study period, they had a diagnostic code for one of three conditions (ASD, CP or FASD) from a health service (i.e., physician visits, or emergency room visits, or hospitalizations), or accessed disability support programs for ASD, CP or FASD. Results The results showed different service use patterns for the three conditions: (1) a higher proportion of children with ASD were students with special needs compared to children with FASD and CP; (2) a lower proportion of children with FASD received FSCD services compared to children with ASD and CP; (3) a higher proportion of children with FASD were involved in the Child Intervention system and were Income Support recipients compared to children with ASD and CP. Moreover, the study showed that there was a decrease in accessing services and programming from Persons with Development Disabilities (PDD) for young Albertans with ASD, CP and FASD from 2005/06 to 2010/11. In contrast, the use of another adult disability program that provides only financial assistance, Assured Income for Severely Handicapped, increased over time. Conclusion/Implications The use of population-based linked administrative data allows a comprehensive and comparative study for government service use patterns. The findings have implications for cross-ministry policy and program development, resource allocation, and service coordination and delivery to young Albertans with ASD, CP and FASD.